2021
DOI: 10.1007/s11262-021-01853-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterisation of the influenza viruses circulating in Bulgaria during the 2019–2020 winter season

Abstract: Influenza viruses have a high potential for genetic changes. The objectives of this study were to analyse influenza virus circulation in Bulgaria during the 2019/2020 season, to perform a phylogenetic and molecular analyses of the haemagglutinin (HA) and neuraminidase (NA) sequences of representative influenza strains, and to identify amino acid substitutions compared to the current vaccine strains. Seasonal influenza viruses A(H3N2), A(H1N1)pdm09 and B/Victoria-lineage were detected using a real-time RT-PCR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Of the remaining 587 articles, 547 were discarded for not matching the inclusion criteria (of these, 62 were not further considered since no reported influenza cases were type B), 7 for being based on the WHO FluNet and/or GISAID database, 3 for being previous reports from the GIHSN, and 4 because of overlap with more recent and/or larger articles based on the same data sources. A total of 26 articles were included in the systematic review: their main characteristics are reported in Table 1 [ Soldevila 2022, Murillo-Zamora 2021, Korsun 2021, Panatto 2021, Pablo-Marcos 2020, Miron 2021, Hu 2021, Omer 2022, Olson 2022, Auvinen 2022, Kuzmanovska 2021, Wagatsuma 2022, Heinzinger 2021, Rios-Silva 2022, Suntronwong 2021, da Costa 2022, Melidou 2020, Huang 2022, O’Neill 2022, Kolosova 2022, Peck 2023, Chon 2023, Merced-Morales 2022, Melidou 2022, Sominina 2022, Song 2022 ]. Europe was the most represented area (12 articles, of which 2 reported findings from multiple countries in the WHO European Region), followed by Asia (n=6), North America (n=5), and Oceania and South America (n=1 each).…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 587 articles, 547 were discarded for not matching the inclusion criteria (of these, 62 were not further considered since no reported influenza cases were type B), 7 for being based on the WHO FluNet and/or GISAID database, 3 for being previous reports from the GIHSN, and 4 because of overlap with more recent and/or larger articles based on the same data sources. A total of 26 articles were included in the systematic review: their main characteristics are reported in Table 1 [ Soldevila 2022, Murillo-Zamora 2021, Korsun 2021, Panatto 2021, Pablo-Marcos 2020, Miron 2021, Hu 2021, Omer 2022, Olson 2022, Auvinen 2022, Kuzmanovska 2021, Wagatsuma 2022, Heinzinger 2021, Rios-Silva 2022, Suntronwong 2021, da Costa 2022, Melidou 2020, Huang 2022, O’Neill 2022, Kolosova 2022, Peck 2023, Chon 2023, Merced-Morales 2022, Melidou 2022, Sominina 2022, Song 2022 ]. Europe was the most represented area (12 articles, of which 2 reported findings from multiple countries in the WHO European Region), followed by Asia (n=6), North America (n=5), and Oceania and South America (n=1 each).…”
Section: Resultsmentioning
confidence: 99%
“…About half of the subclade 6B.1A.5 viruses detected in NSW presented additional amino acid substitutions D187A and Q189E (located within antigenic site Sb), which were not reported in Australia's previous season. Interestingly, these variants became more prevalent in Northern Hemisphere countries during the 2019–2020 winter season 38,44,45 . Additionally, this subclade was shown to have more substitutions in its antigenic regions compared with other subclades 32,38,44,46 .…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, these variants became more prevalent in Northern Hemisphere countries during the 2019–2020 winter season 38,44,45 . Additionally, this subclade was shown to have more substitutions in its antigenic regions compared with other subclades 32,38,44,46 . Despite these identified viruses harboured multiple additional amino acid substitutions compared with the 2019 vaccine strain, these did not seem to have a significant impact on vaccine effectiveness, which was estimated at 62% (95% CI: 39–78) in Australia in 2019 42 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The epidemic types of pdm09 were clade 6B.1A and subclades 6B.1A1, 6B.1A5, and 6B.1A6 in 2017-2019 in Thailand. The pdm09 viruses of 6B.1A5A have been circulating in Bulgaria since 2019 (Korsun et al, 2021;Suntronwong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%